DevMetrics: An Experience Report on Effort Estimation in Software Maintenance Using a Jira-Integrated Framework - Andrade, Marcos; Brittes, Marisangela; Souza, Alinne; Pegorini, Jessica (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
This paper presents the development of DevMetrics, a generic system designed to support effort estimation in software maintenance activities. The tool combines textual similarity (Jaccard index) with statistical regression (linear and exponential), normalized using the Fibonacci sequence, and integrates seamlessly with Jira. A case study was conducted in a medium-sized software house using MMRE and PRED(0.25) metrics, along with Likert-based surveys to assess team perception. Results show that the tool enhances estimation accuracy and planning predictability, especially when teams adopt standardized task descriptions and ensure historical data quality.